PREVALENCE OF TYPE D PERSONALITY AND ITS ASSOCIATION WITH CARDIOVASCULAR DISEASES AND THEIR RISK FACTORS ACCORDING TO THE ESSE STUDY CONDUCTED IN KEMEROVO REGION - A. N. Sumin; O. I. Raykh; E. V. Indukaeva; G. V. Artamonova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the prevalence of type D personality and its association with cardiovascular diseases and their risk factors in Russia’s population.Material and methods. The research was conducted within the framework of multicentre epidemiological study ESSE-RF. The total sample size was 1610 patients (men and women aged 25-64 years). The type D personality was assessed using questionnaire DS-14. The patients were divided into two groups: patients with the presence of type D personality (n=231) and patients without type D personality (n=1379). Arterial hypertension, smoking, diabetes, hypercholesterolemia and obesity were accepted as major cardiovascular risk factors that are well studied and used in the most of the known cardiovascular risk assessment models.Results. Type D personality was detected in 231 (14.3%) patients. Among patients with the type D personality as compared with those without one arterial hypertension (r=0.033), ischemic heart disease (r=0.053), vascular diseases of a brain (r=0.041) were revealed more often. Type D personality was associated with such risk factors as diabetes, smoking duration, low physical activity, overweight and obesity.Conclusion. The study results can be useful in the development and carrying out programs of primary and secondary prevention of cardiovascular diseases.